Spatio-temporal variation and prediction of ecological quality based on remote sensing ecological index – a case study of Zhanjiang City, China - Wang, Jing; Wang, Jia; Xu, Jiangqi (Frontiers in Ecology and Evolution, 2023)
Abstract: A significant portion of Zhanjiang City's ecological land areas have been reduced as a result of the city's growing urbanization, which has caused the city's ecological environment quality to decline. Therefore, it is crucial to statistically evaluate and forecast changes in Zhanjiang City's ecological environment quality. In order to monitor the quality of the ecological environment, the remote sensing ecological index (RSEI) is frequently utilized. In this study, the Landsat series satellite pictures from 2000, 2005, 2009, 2015, and 2020 were used. The Normalized Differential Vegetation Index (NDVI), Wetness (WET), Normalized Differential Build-up and bare Soil Index (NDBSI), and Land Surface Temperature (LST) were the four indicators utilized in the RSEI to quantitatively evaluate the changes in ecological environment quality in Zhanjiang City. The results are as follows. 1) The mean RSEI values for the years 2000, 2005, 2009, 2015, and 2020 are respectively 0.901, 0.901, 0.903, 0.684, and 0.758. Additionally, Zhanjiang has an excellent overall ecological environment. However, in terms of spatial differences, the ecological environment quality in the city's center is significantly and typically higher than that in other areas, while that in its coastline region is much and generally worse. The lower RSEI index for development sites in the coastal zone area is proof that the RSEI index can reflect the deteriorating environment of urban areas in the coastline zone from 2000 to 2020. According to this outcome, the RSEI can be used to evaluate the ecological environment quality of Zhanjiang city.2) The ecological environment changes in the study area are "substantially better", "better," "no change," "worse," and "much worse," respectively, according to the difference in RSEI processed between 2000 and 2020. These changes were 1.80%, 0%, 0.17%, 3.67%, and 94.35%. The ecological environment has changed "much worse" in Zhanjiang City. This demonstrates that between 2000 and 2020, Zhanjiang City's ecological environment quality substantially decreased. 3) The regression produced the following equation for the association, which was significant at the 0.053 level: 100*Rsei=131.658-11.704*IS(R=0.823). The remote sensing ecological index for Zhanjiang in 2035 is 0.826 when the city's planned population and area are added together.